IRRIGATION INVESTMENTS IN SMALLHOLDER COCONUT FARMING IN KERALA INDIA - LATHA BASTINE, C.; PALASISAMI, K. (International Coconut Community, 1995)
An evaluation of the irrigation investments in smallholder coconut crop in Kerala State in India showed that the share of irrigation costs to total costs was 25‑50 percent in small irrigated holdings. Yhe average variable cost of irrigation was Rs. 1,667.36 and the average capital cost was Rs. 1,031.49 per hectare. The irrigation investments showed wide variations among holdings of different land categories and also different sources qf irrigation.